(untitled) (Bangladesh Rice Journal, 2026)
Increasing cropping intensity increases nutrient mining from the soil, especially potassium (K), if nutrient management is not properly maintained. A field experiment was conducted at Hajee Mohammad Danesh Science and Technology University (HSTU) farm soil, Dinajpur district under the Agro Ecological Zone (AEZ 1) the Old Himalayan Piedmont Plain soil in Boro 2020-21 to evaluate the soil test-based K fertilizer application on Boro rice to increase rice yield as well as maintain soil fertility. Six potassium doses namely, K control, 50%, 75%, 100%, 125% and 150% of soil test based (STB) K, were tested with balanced doses of other chemical fertilizers. Rice growth, yield, and yield-contributing characters were recorded during the panicle initiation and maturity stages of rice, which were greatly influenced by potassium fertilizer application. The grain yield increased significantly with increasing K rates up to 100% STB dose, and excess K application did not show any yield advantage. The N, P and K uptake and the K use efficiencies were influenced largely by the right amount of K application. The optimum K fertilizer dose was around 106 kg K ha-1 for the deficient piedmont rice soil. The 100% STB K fertilization might be suitable for obtaining higher rice yield and maintaining soil fertility in the HSTU farm soil under the Old Himalayan Piedmont Plain of AEZ 1. Bangladesh Rice J.28(1): 91-99, 2024